Dr. John Matthai (1886–1959): between 'Bombay Plan' and 'Planning Commission'. Issue 1 (2nd January 2020) - Ankit, Rakesh
ABSTRACT: Dr John Matthai held key ministerial offices in New Delhi during a time of transition from pre- to post-independent India. He was Finance Minister twice (1946, 1948–50) and, in between, held the portfolios of Industry & Supply and Railway & Transport. Matthai had been an academic in Madras, an administrator with the central government and an economist in Bombay with the Tata group. His wide expertise and diverse experience brought him a range of opportunities in those partisan times, including as Chairman of Taxation Enquiry Committee (1953) and State Bank of India (1955). Matthai's ministerial appointments were unusual, his administrative challenges were unfavourable and his exit from government unexpected. In this article, I argue that his short-lived and scattered ministerial life and the record he left of it provides a unique vantage from which to view the interim times of 1946–1950 in India, with their paradigm of 'continuity and change'.